Remote Learning During COVID-19 : Lessons from Today, Principles for Tomorrow - Munoz-Najar, Alberto (World Bank, Washington, DC, 2021)
School closures during COVID-19 (coronavirus) led to an unprecedented global experiment in the delivery of remote learning. This report seeks to assess what lessons can be drawn from experiences of remote learning during COVID-19 in K-12 education, with a focus on low- and middle-income countries. It focuses on the period from March 2020 to October 2021 and addresses the following key questions: 1. Was remote learning during COVID-19 taken up and if so, was it effective That is, did children learn as much as they did during pre-pandemic, in-person learning 2. What lessons can governments derive from this wide-spread experience 3. How might policymakers use these lessons to reimagine learning as schools begin to reopen This report is part of a larger effort led by the World Bank to provide guidance and technical assistance to optimize country effectiveness in the design and execution of remote learning strategies. It has been developed in conjunction with Remote Learning During the Global School Lockdown: Multi-Country Lessons, a qualitative study conducted between May and November 2020 to understand the perceived effectiveness of remote and remedial learning solutions implemented across 17 countries.